New Trends in Internal Migration in China: Profiles of the New‐generation Migrants. Issue 1 (16th January 2018) - Zhao, Liqiu; Liu, Shouying; Zhang, Wei
Abstract: Three decades since the first wave of rural–urban migration, the new generation of migrant workers has become the main force of internal migration in China. The present paper comprehensively explores the profiles of the new generation of migrant workers in urban China. We find that the "new generation" migrants are more educated and skilled, and are likely to work in manufacturing and service industries than in the construction industry. Moreover, they tend to allocate more time to non‐farm activities and have more months away from home per year in urban areas. In contrast to their predecessors, they tend to migrate to urban areas with their spouses, consume more in urban areas and send less money back home. Our findings suggest that the differences in features between the new generation of rural migrants and urban residents have become smaller and the integration of rural migrants into urban China has taken place gradually.